Short-term antithrombotic strategies after left atrial appendage occlusion: a systematic review and network meta-analysis - Wang, Li-Man; Chen, Yan; Xu, Li-Li; Dai, Meng-Fei; Ke, Yi-Jun; Wang, Bao-Yan; Zhou, Lin; Zhang, Ji-Fan; Wu, Zhang-Qi; Zhou, Yu-Jie; Gu, Zhi-Chun; Xu, Hang (Frontiers in Pharmacology, 2023)
Background Percutaneous left atrial appendage occlusion (LAAO) has emerged as a stroke prevention strategy in patients with nonvalvular atrial fibrillation (NVAF), and patients were required to receive antithrombotic therapy post-procedure. However, the optimal antithrombotic strategy after LAAO remain controversial. This study explored the safety and efficacy of different antithrombotic strategies after LAAO through a network comparison method.We systematically searched the Medline, Embase, and Cochrane Library for studies that reported the interested efficacy and safety outcomes (stroke, device-related thrombus (DRT), and major bleeding) of different antithrombotic strategies (DAPT [dual antiplatelet therapy], DOACs [direct oral anticoagulants] and VKA [vitamin k antagonist]) in patients who had experienced LAAO. A pairwise and network meta-analysis was performed to the interested outcomes. Risk ratios (RRs) with their confidence intervals (CIs) were calculated using a random-effect model. The rank of the different strategies was calculated using the surface under the cumulative ranking curve (SUCRA).Finally, 10 observational studies involving 1674 patients were included.There was no significant difference in stroke, DRT, and major bleeding among the different antithrombotic strategies (DAPT, DOACs and VKA). Furthermore, DAPT ranked the worst in terms of stroke (SUCRA: 19.8%), DRT (SUCRA: 3.6%) and major bleeding (SUCRA: 6.6%). VKA appeared to be superior to DOACs in terms of stroke (SUCRA: 74.9% vs. 55.3%) and DRT (SUCRA: 82.3% vs. 64.1%) while slightly inferior to DOACs in terms of major bleeding (SUCRA: 71.0% vs. 72.4%).No significant difference was found among patients received DAPT, DOACs, and VKA in terms of stroke, DRT, and major bleeding after LAAO. The SURCA indicated that DAPT was ranked the worst among all antithrombotic strategies due to the higher risk of stroke, DRT, and major bleeding events, while VKA were ranked the preferred antithrombotic strategy. However, DOACs are worthy consideration due to the advantages of convenience.